Risk factors for and clinical outcome of congenital cytomegalovirus infection in a peri-urban West-African birth cohort. - Marianne A B van der Sande; Steve Kaye; David J C Miles; Pauline Waight; David J Jeffries; Olubukola O Ojuola; Melba Palmero; Margaret Pinder; Jamila Ismaili; Katie L Flanagan; Akum A Aveika; Akram Zaman; et al. (PLoS ONE)
Background Congenital cytomegalovirus (CMV) infection is the most prevalent congenital infection worldwide. Epidemiology and clinical outcomes are known to vary with socio-economic background, but few data are available from developing countries, where the overall burden of infectious diseases is frequently high. Methodology/principal findings As part of an ongoing birth cohort study in The Gambia among term infants, urine samples were collected at birth and tested by PCR for the presence of CMV DNA. Risk factors for transmission and clinical outcome were assessed, including placental malaria infection. Babies were followed up at home monthly for morbidity and anthropometry, and at one year of age a clinical evaluation was performed. The prevalence of congenital CMV infection was 5.4% (40/741). A higher prevalence of hepatomegaly was the only significant clinical difference at birth. Congenitally infected children were more often first born babies (adjusted odds ratio (OR) 5.3, 95% confidence interval (CI) 2.0-13.7), more frequently born in crowded compounds (adjusted OR 2.9, 95%CI 1.0-8.3) and active placental malaria was more prevalent (adjusted OR 2.9, 95%CI 1.0-8.4). These associations were corrected for maternal age, bed net use and season of birth. During the first year of follow up, mothers of congenitally infected children reported more health complaints for their child. Conclusions/significance In this study, the prevalence of congenital CMV among healthy neonates was much higher than previously reported in industrialised countries, and was associated with active placental malaria infection. There were no obvious clinical implications during the first year of life. The effect of early life CMV on the developing infant in the Gambia could be mitigated by environmental factors, such as the high burden of other infections.